ANALISIS INDRA PENGLIHATAN IKAN KERAPU MACAN (Epinephelus fuscoguttatus) DAN HUBUNGANNYA DALAM MERESPONS UMPAN - M Riyanto; Ari Purbayanto; D S.S. Natsir (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2011)
The visual organ in fish has an important role in ensuring its survival. Fish can respond to bait or food with its visual organ. The objectives of this research are to analyse the visual performance of grouper (cone cell morphology, the visual axis, and visual acuity) and to analyse the relation between visual senses with fish behavior response to the bait. This research was conducted in the laboratory by means of the determination of fish retina histology method and behavior of fish. The morphology retina of grouper consists of a single cone and double cone which form a mosaic structure, the visual axis was identified at upper-fore with the angle of 26.8o.The visual acuity of grouper was low in index values with ranged from 0.06 to 0.07 for fish with a total length of 200 to 300 mm, the maximum sighting distance to the bait with the diameter of 20 mm size ranged from 3.93 to 4.74 m, the bait with 25 mm diameter size range from 4.91 to 5.92 and bait with a diameter of 30 mm size ranged from 5.89 to 7.11 m. The frequency of fish closed the bait distance of 30 cm was 45.83%, 25 cm was 33.33% and 20 cm was 20.83%, respectively.